Iraqi Bauxite and Porcalinite Rocks Based Refractory, Preparation and Studying Properties - Merzah, Amel S. (Al-Khwarizmi Engineering Journal, 2017)
Abstract Locally natural occurring Iraqi rocks of Bauxite and Porcelanite (after pre calcinations at 1000oC for 1hr) were used, with the addition of different proportions of MgO and Al2O3, to prepare refractory materials. The effects of these additives on the physical and thermal properties of the prepared refractories were investigated. Many batches of Bauxite/MgO, Bauxite/Al2O3, Bauxite/MgO/Al2O3, and Porcelanite/ MgO/Al2O3 were prepared. The mixture is milled and classified into different size fractions; fine (less than 45μm) 40%, middle (45-75μm) 40%, and coarse (75-106μm) 20% . X-ray diffraction technique was used to identify the structure of Bauxite and Porcelanite rocks. The samples were formed by semi dry pressing with the addition of few drops of water as a binder. These samples were sintered at 1100oC for 2hrs. Physical properties (linear shrinkage, density and porosity), and the thermal properties (thermal conductivity, diffusivity and specific heat) were measured for all the prepared samples. The results show the increasing of density is susceptible to the thermal properties, and also the addition of Al2O3 and MgO to the natural rocks have a limited effect, and the values of the parameters above for the natural rocks, were in the levels to be used as a refractory material for lining a metal fusion furnaces and other applications. Keywords: Bauxite, Refractory brick, Porcelanite Stone, Physical properties, Thermal properties.